Phytochemical Constituents and Evaluation of Lipoxygenase Activity of Tetracera macrophylla Twigs Wall.ex Hook.f. & Thoms - Ladeska, Vera; Elya, Berna; Hanafi, Muhammad; Kusmardi, Kusmardi (JSFK (Jurnal Sains Farmasi & Klinis), 2024)
Lipoxygenase is an enzyme that catalyzes the formation of leukotriene, which is involved in various diseases  such as asthma, osteoporosis and atherosclerosis. Inhibition of this enzyme can overcome inflammatory diseases. Tetracera  macrophylla Wall.ex Hook. f.& Thoms plant has shown various biological activities, especially as an anti-inflammatory. This study  aims to analyze phytochemical constituents and evaluate the lipoxygenase activity of Tetracera macrophylla twig extract. The  sample was gradually macerated using n-hexane, ethyl acetate, and methanol. Phytochemical analysis of the extract was carried  out using the LC-MS/MS method. Lipoxygenase assay was performed in vitro using RAW 264.7 macrophage cells induced with  lipopolysaccharide using spectrofluorometry. As a comparison, zileuton, which has been established as a 5-LOX inhibitor and  quercetin, which has the potential as a 5-LOX inhibitor. The results showed that methanol extract of Tetracera macrophylla twigs (RM3) had lower specific LOX activity (0.350 mU/mL) than standard zileuton (7.927 mU/mL) and quercetin (12.837 mU/mL).  Decreased LOX activity can lessen the generation of leukotrienes, which cause inflammation. The study showed that methanol extract of Tetracera macrophylla twigs contains active compounds that can be developed as lipoxygenase inhibitors